2010
DOI: 10.1111/j.1399-5448.2009.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin glycation index: a robust measure of hemoglobin A1c bias in pediatric type 1 diabetes patients

Abstract: Biological variation in A1c is a robust quantitative trait that can be assessed using HGI calculated from routine clinic data. This suggests that HGI could be used clinically for more personalized assessment of complications risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 29 publications
1
71
0
2
Order By: Relevance
“…Individuals with HbA1c values persistently lower or higher than expected relatively to their blood glucose levels have been identified in several studies where blood glucose was estimated based on fasting plasma glucose [22], self- [18,19,31,32], continuous glucose monitoring data [20,33], and classified as high or low glycators. HGI is a measure of the disagreement between the observed value of HbA1c and the one predicted on the basis of blood glucose levels and it is thought to be an indicator of the degree of hemoglobin glycation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with HbA1c values persistently lower or higher than expected relatively to their blood glucose levels have been identified in several studies where blood glucose was estimated based on fasting plasma glucose [22], self- [18,19,31,32], continuous glucose monitoring data [20,33], and classified as high or low glycators. HGI is a measure of the disagreement between the observed value of HbA1c and the one predicted on the basis of blood glucose levels and it is thought to be an indicator of the degree of hemoglobin glycation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HbA1c and other measures of glycaemia reflect different aspects of glucose metabolism, the former is an indicator of the non-enzymatic protein glycation which is dependent of glucose concentration into erythrocytes whereas the latter expresses the physiology of glucose in the extracellular compartment. A mathematical method to measure the discordance between HbA1c and the predicted value of HbA1c based on plasma glucose levels has been developed and termed hemoglobin glycation index (HGI) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Deviations between mean blood glucose and A1C values with continuous glucose monitoring (CGM) have been shown to be consistent in each individual [39][40][41]. These deviations in mean blood glucose and the A1C value are called the glycohemoglobin index (GHI), and the biological variation of A1C has been examined [3,4,42,43]. The G-gap is also reported to be an indicator with biological variation [5,31], and Nayak et al [6] reported that the G-gap has consistent biological variability in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined glycemic indexes with biological variation [37][38][39][40][41][42][43]. Deviations between mean blood glucose and A1C values with continuous glucose monitoring (CGM) have been shown to be consistent in each individual [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Glycated hemoglobin levels are often monitored during T1D as an indicator of long-term elevated glucose levels (Soros et al 2010). Several studies have shown elevated glycation of pancreatic b proteins, including insulin, accompanying T1D (McKillop et al 2002).…”
Section: Autoantigens Created By Posttranslational Modifications In Tmentioning
confidence: 99%